Tumor expression of miR-34a-3p is an independent predictor of recurrence in non-muscle-invasive bladder cancer and promising additional factor to improve predictive value of EORTC nomogram - Juracek, Jaroslav; Stanik, Michal; Vesela, Petra; Radova, Lenka; Dolezel, Jan; Svoboda, Marek; Slaby, Ondrej (Urologic oncology, 2019)
OBJECTIVES: Non-muscle-invasive bladder cancer (NMIBC) is a heterogeneous disease characterized by a high primary tumor recurrence rate. Current prognostic systems used for predicting recurrence in individual patients have limitations and do not consider the biological background of this tumor type. Our study aimed to find microRNAs (miRNAs) associated with NMIBC recurrence. METHODS: Seventy-eight NMIBC patients were prospectively enrolled and divided into exploratory and validation cohorts. Out of these patients, 32 developed recurrence within 18 months after surgery, while 46 did not show any sign of recurrence after 30 months. Expression profiles of 2,578 miRNAs were obtained using Affymetrix miRNA microarrays and candidate miRNAs validated using the individual quantitative reverse-transcription polymerase chain reaction (qRT-PCR). RESULTS: The expression profiling revealed a set of 137 miRNAs differentially expressed between NMIBC patients with and without recurrence (P < 0.05). In the validation phase, miR-34a-3p had a significantly higher expression in tumors of NMIBC patients without recurrence (P = 0.0155). Decreased expression of miR-34a-3p was associated with significantly shorter recurrence-free survival (P = 0.009). Cox regression analysis confirmed that miR-34a-3p is an independent biomarker associated with a lower risk of recurrence (hazard ratio (HR) = 0.3184, 95% confidence interval = 0.003-0.681, P = 0.0258). Combination of miR-34a-3p and European Organization for Research and Treatment of Cancer risk score into one predictive model enabled to predict individual risk of recurrence with high statistical significance and analytical performance (P < 0.0001; area under curve = 0.8368; sensitivity 83%, and specificity 75%). CONCLUSIONS: Our data suggest that miR-34a-3p is an independent biomarker of NMIBC recurrence and a promising candidate for further independent validations as an additional factor to improve predictive value of European Organization for Research and Treatment of Cancer nomogram.
Keywords: Nomograms; regulace genové exprese u nádorů; Humans; lidé středního věku; Oligonucleotide Array Sequence Analysis; MicroRNAs; Predictive Value of Tests; Biomarkers, Tumor; cystoskopie; Female; Aged; močový měchýř; Cystectomy; senioři; lidé; nomogramy; přežití bez známek nemoci; nádorové biomarkery; Cystoscopy; ženské pohlaví; Kaplanův-Meierův odhad; Male; nádory močového měchýře; Middle Aged; prediktivní hodnota testů; prognóza; stanovení celkové genové exprese; Urinary Bladder; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Aged, 80 and over; Disease-Free Survival; senioři nad 80 let; mikro RNA; Kaplan-Meier Estimate; lokální recidiva nádoru; Gene Expression Profiling; cystektomie; mužské pohlaví; prospektivní studie; Gene Expression Regulation, Neoplastic; Urinary Bladder Neoplasms; Neoplasm Recurrence, Local; Prognosis; Prospective Studies